All Days 2012
DOI: 10.4043/23714-ms
|View full text |Cite
|
Sign up to set email alerts
|

Petermann Ice Island 'A' Survey Results, Offshore Labrador

Abstract: In August 2010 a 265 km2 ice island calved from the Petermann Glacier innorthern Greenland. Soon after the initial calving event the mass broke intoseveral pieces, some of which exited Baffin Bay and drifted south toward theLabrador coast. By June 2011 PII-A, a large fragment of the initial PetermannIce Island, was situated offshore Labrador and in one week it had moved 225 kmdown the coast. Concern arose that if PII-A continued its trajectory it couldreach the Grand Banks by August 2011, posing a potential ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 4 publications
1
35
2
Order By: Relevance
“…The recent decline in Arctic summer sea ice extent has led to an increased usage of the Arctic for commercial shipping, as well as renewed efforts in hydrocarbon exploration in the region [Smith and Stephenson, 2013;Hossain and Rao, 2014]. The threat that icebergs still pose to ships and offshore structures continues to fuel interest in iceberg trajectories and decay mechanisms [Halliday et al, 2012;Peterson et al, 2012;Turnbull et al, 2015]. Similiarly, recent efforts to couple numerical ocean models to land-ice models have led to an increased interest in Arctic and Antarctic icebergs [Martin and Adcroft, 2010;Hunke and Comeau, 2011;Coogle, 2013].…”
Section: Introductionmentioning
confidence: 99%
“…The recent decline in Arctic summer sea ice extent has led to an increased usage of the Arctic for commercial shipping, as well as renewed efforts in hydrocarbon exploration in the region [Smith and Stephenson, 2013;Hossain and Rao, 2014]. The threat that icebergs still pose to ships and offshore structures continues to fuel interest in iceberg trajectories and decay mechanisms [Halliday et al, 2012;Peterson et al, 2012;Turnbull et al, 2015]. Similiarly, recent efforts to couple numerical ocean models to land-ice models have led to an increased interest in Arctic and Antarctic icebergs [Martin and Adcroft, 2010;Hunke and Comeau, 2011;Coogle, 2013].…”
Section: Introductionmentioning
confidence: 99%
“…The TIM was run with GEM model data (TIM GEM ) and the same DDFs as TIM AWS-Val and TIM AWS-Fit for operational validation. The TIM model and 'optimal' DDF calculated for the entire Berghaus dataset were validated by running the TIM on another ice island located in the Eastern Canadian Arctic in 2011, PII-A, using GEM model T a data and surface ablation records reported by Halliday et al (2012). This model run is referred to as TIM-PIIA GEM .…”
Section: Temperature Index Melt Modelmentioning
confidence: 99%
“…This increases to approximately 30% for an ice island with a 10 km waterline (Ballicater Consulting Ltd., 2012). An example of the mass loss by surface ablation for an ice island is provided by Halliday et al (2012) who document the surface ablation observed for PII-A, a product of the 2010 Petermann Glacier calving event (Johannessen et al, 2011). This ice island was visited twice between June and July 2011 when adrift off the coast of Labrador.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations